Karyotype evolution in the Termitidae (Isoptera) - Martins, Vanderlei Geraldo [UNESP] (My University, 1999)
The karyotypes of 15 species of Termitidae were analyzed. All of them are X1X2Y1Y2 (male) and X1X1X2X2 (female). With the exception of Neocapritermes opacus with 2n=40, the remaining species are 2n=42 in both sexes, a karyotype similar to those described for African species by other authors. The sex determining mechanism probably originated before the split up of Gondwanaland, in a single event, early during the karyotype evolution of the family Termitidae by means of a reciprocal translocation that involved the primitive Y and a chromosome from an autosomal pair.